Significance of coconut in Koli community - Mumbai Archive Project Team (Jio Institute, 2024)
The Koli community has a deep connection to the sea and marine life. The coconut holds significant cultural, religious, and economic importance in Koli culture. On the day of Maha Shivaratri, a special coconut is brought to the temple, protected by an umbrella, a symbol of royalty.